Effect of Processing Variables on Anthocyanin and Total Polyphenol Extraction from Water Caltrop (Trapa bispinosa) Hull - Adhikari, Babita; Shrestha, Ojeswi Krishna (Himalayan Journal of Science and Technology, 2018)
Anthocyanins are water soluble pigments responsible for the brilliant orange red through deep purple colors in flower and fruits. The effects of different extraction variables (pH, particle size, temperature and time, extraction method) on anthocynin, total polyphenol content and antioxidant of the extracts were studied. The anthocyanin content of fresh and dried (55 °C for 2 h) water caltrop hull were 68.68 and 44.38 μg/100 g d.b. respectively. Temperature, particle size and pH played a significant role (p<0.05) in aqueous extraction of anthonycinin. The optimum aqueous extraction condition were pH of 4.49, particle size of 300 μm, temperature of 67.2 °C and time of 25.38 min which gave 70.3% anthocynin extraction. There was a significant effect of extraction method (acidified ethanol, acidified ethanol and pH differential methods) and particles size on anthocynin extraction (p<0.05). The total polyphenol content in the aqueous extracts from water caltrop hull powder of 300, 690 and 1080 μm were in the range of 55.02-60.31 mg GAE/g dm. The extraction of total polyphenol from 300 μm was significantly different from 690 and 1080 μm particle sizes, while there was no significant difference between from 690 and 1080 μm respectively (p>0.05). The particle size had a significant effect (p<0.05) on the antioxidant activity of the extract and the values ranged from 173.36 μg/mL to 193.69 μg/mL.